2003
DOI: 10.1038/sj.cgt.7700618
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tumor immunogenicity through coupling cytokine expression with antigen presentation

Abstract: The density of tumor antigen in conjunction with major histocompatibility complex (MHC) class I molecules on the cell surface affects cytotoxic T cell (CTL) function in an active antitumor immune response. Thus, methods to enhance antigen expression/ presentation could augment the effect of cancer immune therapy. In the present study, we investigated the feasibility of modifying a cytokine signal peptide with a tumor antigenic epitope. We inserted the genes encoding the MHC class I-restricted antigenic epitope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Heat-denatured ovalbumin also modulates interleukins' (IL) production by downregulating IL-4 and upregulating IL-10, 12, and 17. Ovalbumin-derived peptides corresponding to amino acids in position 77–84 and 126–134 also enhances the phagocytic activity of macrophages ( 57 ) and are reported to enhance immunotherapy ( 50 , 53 , 58 ). Ovotransferrin, another egg white protein, has been shown to stimulate the production of IL-6 and metalloproteinase (MMP) in HD 11 chicken macrophages ( 59 ).…”
Section: Egg As An Immune-enhancing Foodmentioning
confidence: 99%
“…Heat-denatured ovalbumin also modulates interleukins' (IL) production by downregulating IL-4 and upregulating IL-10, 12, and 17. Ovalbumin-derived peptides corresponding to amino acids in position 77–84 and 126–134 also enhances the phagocytic activity of macrophages ( 57 ) and are reported to enhance immunotherapy ( 50 , 53 , 58 ). Ovotransferrin, another egg white protein, has been shown to stimulate the production of IL-6 and metalloproteinase (MMP) in HD 11 chicken macrophages ( 59 ).…”
Section: Egg As An Immune-enhancing Foodmentioning
confidence: 99%
“…Several egg white proteins and peptides have demonstrated immunomodulating activity. Ovalbumin has been found to induce the release of tumor necrosis factor (TNF) α in a dose-dependent manner in vitro, when modified with dicarbonyl methylglyoxyl (), and immunogenic ovalbumin peptides have been used to enhance immune responses for cancer immunotherapy ( ). Tezuka and Yoshikawa () found that the phagocytic activity of macrophages was increased by the addition of ovalbumin peptides, OA 77−84 and OA 126−134, derived from peptic and chymotryptic digestions, respectively.…”
Section: Egg Whitementioning
confidence: 99%
“…Cytokine-based tumor immuno-gene therapy has been intensively investigated in order to develop effective cancer therapy methods [18]. A requisite component for improving gene-based therapies includes tumor suppressor genes that exhibit cancer constrained inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, the K562, THP-1, and MEG-01 cells were infected with recombinant adenoviruses for 48 h and then collected to extract the total RNA with Trizol Reagent (Invitrogen, Carlsbad, CA, USA). The first cDNA strand was synthesized using Oligo d(T) 18 . The PCR primers specific for IL-24 were described above.…”
Section: Rt-pcrmentioning
confidence: 99%